Penggunaan CROPWAT 8.0 untuk Menentukan Kebutuhan Air Irigasi Tanaman Tomat pada Tanah Regosol di Kawasan Ternate Utara, Provinsi Maluku Utara - Suleyman, Suleyman (Cannarium, 2024)
Tomato is an important crop in Ternate, North Maluku Province, Indonesia. This study aimed to determine the irrigation water requirements for tomato cultivation on Regosol soil in the North Ternate region using the CROPWAT 8.0 model. Climate data, crop data, and soil data were collected and processed using the CROPWAT 8.0 program. The results showed that the irrigation water requirements varied significantly between the rainy and dry seasons. During the rainy season, the total irrigation water requirement ranged from 60 to 107 mm, while in the dry season, it was much higher, ranging from 130 to 187 mm. This difference was primarily due to the low rainfall during the dry season. Simulations of planting at different periods showed relatively minor variations in crop water requirements, reflecting the stable weather conditions throughout the year in Ternate. The findings of this study can assist local tomato farmers in managing irrigation water more efficiently and effectively, thereby improving crop productivity and reducing the risk of water shortage.